2006
DOI: 10.1093/jb/mvm005
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Neutral Cysteine Protease Bleomycin Hydrolase and its Localization in Rat Tissues

Abstract: A neutral cysteine protease, bleomycin hydrolase (BH), was found to be present in the range 3.7-131.1 ng per mg of rat tissues by enzyme-lined immunosorbent assay (ELISA). Newborn rat skin contained the highest amount of BH, and relatively high levels of BH were detected in the kidney and liver of 6-week-old male rats. The tissue distribution of BH in female rats was similar to that in male rats. Moreover, BH was detected in the extracts of erythrocytes and leukocyte-rich cells as well as in those of rat hemo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Unfortunately, that particular study did not evaluate BH levels in older animals (ie, 1–2 years). 44 Others have shown alterations in BH associated with Alzheimer’s disease, which is a disease of older individuals. 45,46 Therefore, presumably, there could be some changes of BH in lungs of old mice compared with young ones.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, that particular study did not evaluate BH levels in older animals (ie, 1–2 years). 44 Others have shown alterations in BH associated with Alzheimer’s disease, which is a disease of older individuals. 45,46 Therefore, presumably, there could be some changes of BH in lungs of old mice compared with young ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, it had no activity toward any protein substrates including myelin basic protein, azocasein, bovine serum albumin, myoglobin, and cystatin A. The enzyme was co-localized with filaggrin in the upper layers of the stratum corneum, where it was present in large amounts, in mammalian skin (31,(45)(46)(47). These results strongly suggested that BH participated in the release of free amino acids including citrulline in peptides processed from deiminated filaggrin in mammalian skin.…”
Section: Filaggrin Fragmentmentioning
confidence: 96%
“…Once in the cytosol, BLM can be degraded by BLM hydrolase [1]. Different cell lines could have different amount or activity of BLM hydrolase, which could lead to BLM degradation effectiveness [34,35]. Alternatively, different cell lines could show different BLM resistance due to drug accumulation properties or DNA reparation mechanisms [36,37].…”
Section: Different Cell Line Sensitivity To Blmmentioning
confidence: 99%